Analytical and computational analysis of pressure at the nose of a 2D wedge in high-speed flow - Shaikh, Javed S; Kumar, Krishna; Pathan, Khizer Ahmed; Khan, Sher Afghan (Techno Press, 2022)
Supersonic projectiles like rockets, missiles, or aircraft find various applications in the field of defense. The shape of the wings is mainly designed as wedge shape or delta wings for supersonic vehicles. The study of supersonic flows over the wedges and flat plate delta wings around the large scale of incidence angle is considered in the supersonic projectile. In the present paper, the prime attention is to study the pressure at the nose of the plane wedge over the various Mach number and the various angles of incidence. Ghosh piston theory is used to obtain the pressure distribution analytically, and the results are compared with CFD analysis results. The wedge angle and Mach number are the parameters considered for the research work. The range of wedge angle is 50 to 250, and Mach number is 1.5 to 4.0 are considered for the current research work. The analytical results show excellent agreement with the CFD results. The results show that both the parameters wedge angle and Mach number are influential parameters to vary the static pressure. The static pressure increases with an increase in Mach number and wedge angle